Business Planning : GLOMUSH Enterprise / Shaidatul Azia Zailani ...[et al.] - Zailani, Shaidatul Azia; Mukhtar, Siti Fareeza; Shafie, Siti Suhada; Abd Manaf, Siti Rosliza; Ismail, NurHaizuin (2008)
GLOMUSH Enterprise stands for Global, Glow, and Glory Mushroom. This company was established by Nur Haizuin Ismail, Shaidatul Azia Zailani, Siti Fareeza Mukhtar, Siti Rosliza Abd Manaf and Siti Suhada Shafie. This company is a partnership company. We choose this name because of the depth meaning and it can stimulate people to buy our products. Besides, we want to supply our products to international industry step by step. At the first time we introduce and produce oyster mushroom only. This is because we want to see and get the respond from the community in Machang Kelantan area.